2014
DOI: 10.1186/1471-2229-14-58
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation of soybean flower color gene W4 encoding dihydroflavonol 4-reductase 2

Abstract: BackgroundFlower color of soybean is primarily controlled by six genes, viz., W1, W2, W3, W4, Wm and Wp. This study was conducted to investigate the genetic and chemical basis of newly-identified flower color variants including two soybean mutant lines, 222-A-3 (near white flower) and E30-D-1 (light purple flower), a near-isogenic line (Clark-w4), flower color variants (T321 and T369) descended from the w4-mutable line and kw4 (near white flower, Glycine soja).ResultsComplementation tests revealed that the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 24 publications
1
44
0
1
Order By: Relevance
“…Recent reports in anthurium and soybean have confirmed the strong correlation between color intensity and anthocyanin accumulation (Gopaulchan et al 2014;Yan et al 2014). To determine whether this effect also occurred in delphinium, we measured the amounts of anthocyanin in the sepals of the six varieties.…”
mentioning
confidence: 97%
“…Recent reports in anthurium and soybean have confirmed the strong correlation between color intensity and anthocyanin accumulation (Gopaulchan et al 2014;Yan et al 2014). To determine whether this effect also occurred in delphinium, we measured the amounts of anthocyanin in the sepals of the six varieties.…”
mentioning
confidence: 97%
“…Yan et al (2014) reported a w4 mutant line and its w4 nucleotide sequence from a potential wild soybean. This is likely the first true finding of a recessive w4 allele from a wild soybean (G. soja).…”
Section: Discussionmentioning
confidence: 99%
“…However, only one synonymous SNP was identified in the exon region, indicating that the same amino acid sequence was encoded by DFR2 in both YWS415 and W4 soybean accessions in the absence of the transposon insertion (Xu et al, 2010;Yan et al, 2014;Sundaramoorthy et al, 2016). KY744345) of YWS415 covered the postulated full-length coding sequence of DFR2.…”
Section: Nucleotide Sequence and Genetic Analysis Of The Locus Conditmentioning
confidence: 99%
See 1 more Smart Citation
“…The miRNA cca-miR395a targets ATP sulfurylase that involves in sulfur assimilation and improves nutrient content of the plant, Dihydroflavonol-4-reductase enzyme that controls seed coat and flower colour in soybean (Herrmann et al, 2014;Yan et al, 2014). The miRNA cca-miR5219 suppresses the expression of 60S ribosomal protein L9 and peptidyl-prolyl cis-trans isomerase which help in translation elongation and protein peptidyl-prolyl isomerization respectively.…”
Section: Computation Based Identification Of Putative Target Of New Mmentioning
confidence: 99%